A Novel Low-Cost, High-Resolution Camera System for Measuring Peat Subsidence and Water Table Dynamics - Evans, Chris D.; Callaghan, Nathan; Jaya, Adi; Grinham, Alistair; Sjogersten, Sofie; Page, Susan E.; Harrison, Mark E.; Kusin, Kitso; Kho, Lip Khoon; Ledger, Martha; Evers, Stephanie; Mitchell, Zak; et al. (Frontiers in Environmental Science, 2021)
Peatlands are highly dynamic systems, able to accumulate carbon over millennia under natural conditions, but susceptible to rapid subsidence and carbon loss when drained. Short-term, seasonal and long-term peat surface elevation changes closely linked to key peatland attributes such as water table depth (WTD) and carbon balance, and may be measured remotely using satellite radar and LiDAR methods. However, field measurements peat elevation change are spatially and temporally sparse, reliant on low-resolution manual subsidence pole measurements, or expensive sensor systems. Here we describe a novel, simple and low-cost image-based method for measuring peat surface motion and WTD using commercially available time-lapse cameras and image processing methods. Based on almost two years’ deployment of peat cameras across contrasting forested, burned, agricultural and oil palm plantation sites in Central Kalimantan, Indonesia, we show that the method can capture extremely high resolution (sub-mm) and high-frequency (sub-daily) changes in peat surface elevation over extended periods and under challenging environmental conditions. WTD measurements were of similar quality to commercially available pressure transducers. Results reveal dynamic peat elevation response to individual rain events, consistent with variations in WTD. Over the course of the relatively severe 2019 dry season, cameras in deep-drained peatlands recorded maximum peat shrinkage of over 8 cm, followed by partial rebound, leading to net annual subsidence of up to 5 cm. Sites with higher water tables, and where borehole irrigation was used to maintain soil moisture, had lower subsidence, suggesting potential to reduce subsidence through altered land-management. Given the established link between subsidence and CO2 emissions, these results have direct implications for the management of peatlands to reduce high current greenhouse gas (GHG) emissions. Camera-based sensors provide a simple, low-cost alternative to commercial elevation, WTD and GHG flux monitoring systems, suitable for deployment at scale, and in areas where existing approaches are impractical or unaffordable. If ground-based observations of peat motion can be linked to measured GHG fluxes and with satellite-based monitoring tools, this approach offers the potential for a large-scale peatland monitoring tool, suitable for identifying areas of active carbon loss, targeting climate change mitigation interventions, and evaluating intervention outcomes.